2018
DOI: 10.4018/ijmbl.2018010101
|View full text |Cite
|
Sign up to set email alerts
|

A Thematic Review of Blended Learning in Higher Education

Abstract: This article reviews the international literature on blended learning in view of establishing its thematic trends in higher education. The systematic review through PRISMA, sought to answer three research questions: First, how have publications evolved from 2000 to 2016 in blended learning in higher education? Secondly, what themes are frequently published in blended learning since 2000 to 2016? Thirdly, what are the emerging sub-themes in the blended learning publications in higher education? A thematic resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 26 publications
1
25
0
Order By: Relevance
“…Blended learning is a common approach in the Higher Education sector where students learn both on and off-campus, and consequently there is myriad research on this topic (Pima et al, 2018). Whereas emerging literature about the school sector has been described as limited and lacking in controls (Poirier et al, 2019).…”
Section: Learning Design Modelsmentioning
confidence: 99%
“…Blended learning is a common approach in the Higher Education sector where students learn both on and off-campus, and consequently there is myriad research on this topic (Pima et al, 2018). Whereas emerging literature about the school sector has been described as limited and lacking in controls (Poirier et al, 2019).…”
Section: Learning Design Modelsmentioning
confidence: 99%
“…Blended learning is a common approach in the Higher Education sector where students learn both on and off-campus, and consequently there is a myriad of research on this topic (Pima et al, 2018). Emerging literature in the school sector has been described as limited and lacking in controls (Poirier et al, 2019).…”
Section: Blended Learning Researchmentioning
confidence: 99%
“…Some research has indicated that BL contributes to improving teaching-learning processes, while other research has found no significant differences with respect to alternative models. A study analyzing 45 publications [14] identified research trends between the year 2000 and 2016 [15], focusing on digital tools or platforms to foster interaction between people and electronic devices. Likewise, and to contextualize our analysis, other reviews have been analyzed including one involving books and chapters [16] and another based on 205 academic theses and final master's projects [17].…”
Section: Introductionmentioning
confidence: 99%